Diagnóstico preliminar sobre as bibliotecas municipais de São Carlos no contexto dos objetivos do desenvolvimento sustentável da Agenda 2030 - Marcomini, Kelly Cristina da Silva (Universidade Federal de São Carlos, 2024)
United Nations (UN) established the 2030 Agenda, a global action plan aimed at promoting sustainable economic development and eradicating poverty, with 17 Sustainable Development Goals (SDGs) to be achieved by the end of 2030. In this context, it is argued that public libraries play a strategic role in fostering the achievement of these goals. Based on this premise, this research aims to develop a preliminary diagnosis of how the municipal libraries of São Carlos align with the 2030 Agenda. To achieve this, the following specific objectives were outlined: to identify and describe the actions carried out by the municipal libraries of São Carlos that align with the SDGs of the 2030 Agenda. This is an exploratory study that includes a literature review on the relationship between libraries and the 2030 Agenda, as well as a historical analysis of the city of São Carlos, particularly regarding its educational trajectory and the training of librarians. Data collection was guided by direct observation of the social media platforms of São Carlos' municipal libraries, in order to support the development of the preliminary diagnosis. The results indicate that the city's municipal libraries went through an institutionalization process, culminating in the formation of the São Carlos Integrated Library System (SIBI-São Carlos). This process, which intensified until 2012, promoted relevant actions that can be linked to the potential fulfillment of the SDGs of the 2030 Agenda. However, it is observed that SIBI-São Carlos, as a network of libraries, requires continuous support to stimulate and energize the promotion of social awareness campaigns on the 2030 Agenda.
Preliminary diagnosis of São Carlos municipal libraries in the context of the sustainable development goals of the 2030 Agenda
Keywords: Agenda 2030; Bibliotecas municipais; Objetivos de desenvolvimento sustentável; Sistema de Bibliotecas Municipais de São Carlos; Agenda 2030; Municipal libraries; Sustainable development goals; São Carlos Municipal Library System; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA